Harnessing the Power of Artificial Intelligence in the Accounting Industry: A Case Study of KPMG - Ranjith P V; Sahana Madan; Delon Ang Wern Jian; Kok Ban Teoh; Amisha Siddhu Singh; Varsha Ganatra; Akshay AV; Rajeev Rana; Abhijit Das; Shetty Lavanya Shekar; Padmalini Singh (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2021)
In the ‘New Normal', the accounting industry is experiencing heavy pressure associated with artificial intelligence (AI). The purpose of this study is to examine the ways and how organizations are harnessing the power of artificial intelligence in the accounting industry through the lens of KPMG. There are 39 employees from the KPMG who responded through a structured questionnaire on Google Forms circulated among the employees of the company. The data collected were analyzed and presented in the table of numerical terms. The results showed there is a significant positive relationship between the adaptation of AI in the accounting tasks in KPMG company. The results of this study reflect upcoming AI practices that will be sent to the KPMG to enhance awareness and adopt artificial intelligence applications for better productivity. These findings can help the accountants in clearly understanding how they can use AI technology to improve the accounting standards.